2022
DOI: 10.3390/ijms23136958
|View full text |Cite
|
Sign up to set email alerts
|

KCNN4 Promotes the Stemness Potentials of Liver Cancer Stem Cells by Enhancing Glucose Metabolism

Abstract: The presence of liver cancer stem cells (LCSCs) is one of the reasons for the treatment failure of hepatocellular carcinoma (HCC). For LCSCs, one of their prominent features is metabolism plasticity, which depends on transporters and ion channels to exchange metabolites and ions. The K+ channel protein KCNN4 (Potassium Calcium-Activated Channel Subfamily N Member 4) has been reported to promote cell metabolism and malignant progression of HCCs, but its influence on LCSC stemness has remained unclear. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Subsequently, we found that reducing NCAPH expression could decrease the glycolytic capacity, and the use of the glycolysis inhibitor 2-DG could reverse the promotion of 5-FU resistance and stemness in COAD cell lines caused by NCAPH overexpression. Consistent with this, the use of the glycolysis inhibitor 2-DG in liver cancer can eliminate the increase in liver CSC ratio induced by KCNN4 [34], and PRMT6 deficiency can mediate tumorigenicity and sorafenib resistance [35]. Viewed in toto, our findings ascertained that NCAPH was a key mediator in regulating the glycolytic pathway, enhancing stemness and drug resistance in COAD cells, and targeting glycolysis may be a feasible strategy to inhibit cancer stemness and drug resistance in COAD treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Subsequently, we found that reducing NCAPH expression could decrease the glycolytic capacity, and the use of the glycolysis inhibitor 2-DG could reverse the promotion of 5-FU resistance and stemness in COAD cell lines caused by NCAPH overexpression. Consistent with this, the use of the glycolysis inhibitor 2-DG in liver cancer can eliminate the increase in liver CSC ratio induced by KCNN4 [34], and PRMT6 deficiency can mediate tumorigenicity and sorafenib resistance [35]. Viewed in toto, our findings ascertained that NCAPH was a key mediator in regulating the glycolytic pathway, enhancing stemness and drug resistance in COAD cells, and targeting glycolysis may be a feasible strategy to inhibit cancer stemness and drug resistance in COAD treatment.…”
Section: Discussionsupporting
confidence: 76%
“…These experiments showed that glucose uptake rates were significantly impaired in IK negative BC cells (Fig. 1G), again confirming a previously unknown contribution of IK channels to the accelerated glucose transport and metabolism in BC cells as discussed later in more detail [43][44][45][46].…”
Section: Depletion Of Ik Reduces Glycolytic Activity and Capacity Of ...supporting
confidence: 84%
“…Interestingly, reduced glucose uptake was observed in MMTV-PyMT IK KO BC cells, thereby explaining the lower rates of glycolysis, pyruvate, and lactate production. Interestingly, glucose metabolism and tolerance seem to be dependent on IK channels [44,45]. IK expression correlated with GLUT1 expression patterns, and it was linked to sodium ion-dependent glucose transporters (SGLTs) [43,92,93].…”
Section: Discussionmentioning
confidence: 99%
“… 38 In addition, TME-regulation associated primarily consisted of genes mixture of endothelial-associated and stroma-associated topics with enrichment of distinct genes known to control tumor growth and promote stemness of cancer cells in microenvironment such as KCNN4 , IL6ST , and CD1B . 39 Furthermore, we observed a significant overlap between the gene-gene interactions derived from the interaction topic model and the gene network in the STRING database. 40 Here, 51%, 40%, 18%, 25%, 13%, 12%, and 13% of ligand-receptor pairs ( Z score>4.0 and Pearson correlation coefficient >3.0) matched with gene pairs in the STRING database (combined score >0.3) from lymphoid, myeloid, stroma, endothelial, TME regulation, cancer metastasis, and cancer growth topics, respectively ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 86%